Mengenal Asuransi Syariah Dari Sejarah, Dasar Hukum Sampai Akad Transaksi - Khozainul Ulum (JES (Jurnal Ekonomi Syariah), 2017)
The development of sharia-based insurance is very closely followed by people's understanding of the sharia insurance contract, the position of the parties in the sharia insurance so that each of interest group get legal protection. The legal protection is expected to provide the values of truth, order, justice and benefit both sides party. Sharia insurance or takaful is basically ta’awun agreement between insurance participant and group of people. The aim is to guarantee and protect each other in dealing with the effects of a particular event is not expected that impinge on other participants. Insurance history has existed since the time of BCE and occurs at the time of ancient Egypt that is at the discretion of the Prophet Yusuf. But the existence of Islamic insurance in Indonesia is too late. Takaful in Muslim-majority country has existed since 1979, even with the non-Muslim majority states Indonesia defeated first. For example, in Luxemburg Takaful insurance evolved since 1983. Meanwhile, in Indonesia Islamic insurance start operating in 1995. The contract of sharia insurance is implemented by combining several contracts, namely mudharabah, tabarru, wakalah and hibah in one treaty. At glance, conventional and sharia insurance will appear same. But, in fact it is different. The difference consists in the legal foundation, management, accounting systems, operations and company culture. Keywords: Sharia Insurance, Contract of Kafalah, Conventional Insurance